BLENDED LEARNING/ TEACHING OF ENGLISH IN TERTIARY EDUCATION - Darginavičienė, Irena; Janulienė, Aušra (Verbum, 2015)
The article deals with a research into students’ viewpoints on the usage of blended learning in studies of professional English. Universities are expected to follow contemporary trends of employing ICT for mastering foreign languages. Recent linguistic publications prove that ICT is making great influence on language classrooms. Currently, ‘blended learning‘ is defined as the integrated combination of traditional face-to-face (F2F) learning with online activities. This article presents the findings on students’ viewpoints on the priorities of traditional and e-learning forms. The analysis of the research data revealed that the respondents, who were students of linguistics and law, demonstrated readiness to be involved in various online and traditional classroom activities. The frequencies of positive and negative responses to a specially designed survey are analyzed. Not all the students enjoy e-learning in spite of its advantages, which might be due to their individual likes and dislikes. Statistical treatment of the students’ responses by a means of Software Package for Social Sciences (SPSS) includes the computations of correlation coefficients, which indicate the strength of relationships and their statistical significance. The findings showed that the students’ attitudes to online learning seem to differ for different activities, but they are quite similar at the first sight. Moreover, direct relationships have been observed between the samples of different specializations with the probabilities either 95% or 99%, which are acceptable in the research of Social Sciences. It should be mentioned that negative responses of students seem to depend on their individual approaches to online activities and personal perceptions, i.e. resistance towards online learning might be due to individual likes and dislikes.
Keywords: English for Specific Purposes; blended learning; face-to-face (F2F) learning versus online learning